Conjugal Visit Policy in the Perspective of Indonesian Criminal Law: Between the Fulfillment of Human Rights and the Limits of Islamic Morality - Syafari, Tri; Basto Daeng Robo; Fathurrahim; Sophian Yahya Selajar; Nurhayati Chalil (Dinasti Research, 2025)
This study explores the legal and moral dimensions of conjugal visits within Indonesia’s criminal justice system by examining their position under national law and the potential influence of Islamic morality on correctional policy. It highlights the existing gap between constitutional guarantees of human rights—specifically the right to family life and the satisfaction of biological needs—and the absence of explicit legal provisions allowing conjugal visits for prisoners. Employing a normative legal methodology, this research utilizes legislative, conceptual, comparative, and philosophical approaches, drawing upon sources such as the 1945 Constitution, Correctional Law, Criminal Code, international human rights instruments, and Islamic jurisprudence. The findings indicate that conjugal visits may be recognized as a conditional right aligned with humanitarian principles and rehabilitation objectives, provided that implementation follows strict ethical and procedural safeguards consistent with Islamic teachings that confine sexual relations to lawful marriage. Thus, the regulation of conjugal visits remains possible if framed as a limited privilege integrating human rights with Islamic moral principles. The study’s novelty lies in proposing a reconciliatory policy model that merges socio-psychological, juridical, and human rights perspectives, offering a framework for humane, religiously compliant, and socially appropriate correctional reform in Indonesia.